Monitoring Expired CO2 Kinetics to Individualize Lung-Protective Ventilation in Patients With the Acute Respiratory Distress Syndrome - Suárez-Sipmann, Fernando; Villar, Jesús; Ferrando, Carlos; Sánchez-Giralt, Juan A.; Tusman, Gerardo (Frontiers in Physiology, 2021)
Mechanical ventilation (MV) is a lifesaving supportive intervention in the management of acute respiratory distress syndrome (ARDS), buying time while the primary precipitating cause is being corrected. However, MV can contribute to a worsening of the primary lung injury, known as ventilation-induced lung injury (VILI), which could have an important impact on outcome. The ARDS lung is characterized by diffuse and heterogeneous lung damage and is particularly prone to suffer the consequences of an excessive mechanical stress imposed by higher airway pressures and volumes during MV. Of major concern is cyclic overdistension, affecting those lung segments receiving a proportionally higher tidal volume in an overall reduced lung volume. Theoretically, healthier lung regions are submitted to a larger stress and cyclic deformation and thus at high risk for developing VILI. Clinicians have difficulties in detecting VILI, particularly cyclic overdistension at the bedside, since routine monitoring of gas-exchange and lung mechanics are relatively insensitive to this mechanism of VILI. Expired CO2 kinetics integrates relevant pathophysiological information of high interest for monitoring. CO2 is produced by cell metabolism in large daily quantities. After diffusing to tissue capillaries, CO2 is transported first by the venous and then by pulmonary circulation to the lung. There, after diffusing from capillaries to lung alveoli, it is finally convectively transported by lung ventilation for its elimination to atmosphere. Modern readily clinically available sensor technology integrates information related to pulmonary ventilation, perfusion, and gas-exchange from the single analysis of expired CO2 kinetics measured at the airway opening. Current volumetric capnography (VCap), the representation of volume of expired CO2 in one single breath, informs about pulmonary perfusion, end-expiratory lung volume, dead space, and pulmonary ventilation inhomogeneities, all intimately related to cyclic overdistension during MV. Additionally, the recently described capnodynamic method provides the possibility to continuously measure the end-expiratory lung volume and effective pulmonary blood flow. All this information is accessed noninvasively and breath-by-breath helping clinicians to personalize ventilatory settings at the bedside and minimize overdistension and cyclic deformation of lung tissue.